CHARACTERIZATION OF MULTI-DRUG RESISTANCE LIVESTOCK ACQUIRED METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS (LA-MRSA) ISOLATES FROM DIFFERENT SWINE FARMS IN ENUGU METROPOLIS, NIGERIA - Okolie, Sandra Oluchi; Iroha, Ifeanyichukwu Romanus; Ikpe, Vitalis PO; Peter O, Ugwudike; Victor, Egbuji Jude; Alexander, Idoko (Universal Journal of Pharmaceutical Research, 2022)
Aim and Objective: Globally, livestock animals, particularly swine, calves and poultry are colonized by Livestock acquired methicillin resistant Staphylococcus aureus (S. aureus) (LA-MRSA). This study was aimed at screening for multi-drug resistant in LA-MRSA strains isolated from swine from selected swine farm within Enugu metropolis. Methods: A total of 307 pig nasal swabs samples were collected, from farm A (76), farm B (116) and from C (108) in Enugu metropolis. Then within 1 hour of collection, samples were transferred to the Caritas University Microbiology Laboratory unit for bacteriological analysis using a standard microbiological isolation and identification protocol. Isolated S. aureus and LA-MRSA strain were phenol-typing screened and identified for MRSA using Kirby-Bauer disc diffusion method with 1 μg oxacillin/30μg cefoxitin antibiotic Disc and Tetracycline Disk Test respectively. Antibiogram studies of LA-MRSA against several antibiotic discs and multiple antibiotic resistance indexes were determined. Results: Results showed overall isolation rate of 76.2 % S. aureus comprising of 90.5 %, 80.3 % and 62.9 % in Farm B, Farm A and Farm C respectively, total MRSA detection rate of 125 (40.7%) comprising Farm A 50.0 %, Farm B 46.6 %, Farm C 30.6 %. LA-MRSA were identified in 84(27.4%) of swine with high proportion of 29(38.2 %) in Farm A followed by Farm C30(27.8%) and Farm B 25(21.6 %). LA-MRSA from Farm A Nursery: 27.3%, Weaning 0.0 %, Grower 77.0 % while Farm B Nursery 24.1 %, Weaning 0.0 %, Grower 7.3 %, finisher 100 % and Farm C Nursery 28.0 %, Grower 34.5 % and finisher 53.3 %. LA-MRSA isolates exhibited a significantly (p≤0.05) high % resistance within the range of 50-100 % against tetracycline, erythromycin, cefotaxime, clindamycin, Trimethoprim-Sulfamethoxazole and exhibit MDR with MARI value ≥0.3 but were susceptible to ciprofloxacin 77.8 %, amikacin 100 % and imipenem 100 %. Conclusion: LA-MRSA strains increased levels of MDR phenotype suggest that the emergence of LA-MRSA in swine up keeping could be promoted through veterinary antibiotics. Thus, to prevent antimicrobial resistance in both animals and humans, joint cross-examination of multi-resistant livestock acquired S. aureus, with an incorporated ‘One Health’ advancement are needed for effective curbing and control measures for LA-MRSA infections. Peer Review History: Received: 8 August 2022; Revised: 12 September; Accepted: 23 October; Available online: 15 November 2022 Academic Editor: Prof. Dr. Gorkem Dulger , Duzce University, Turkey, gorkemdulger@yandex.com Reviewers: Dr. U. S. Mahadeva Rao, Universiti Sultan Zainal Abidin, Terengganu Malaysia, raousm@gmail.com Prof. Cyprian Ogbonna ONYEJI, Obafemi Awolowo University, Ile-Ife, Nigeria, conyeji@oauife.edu.ng